The blocks of theq-Schur algebra - Cox, A (Elsevier, 1998)
In [11] , Donkin determined the blocks of the classical Schur algebras in positive characteristic from the blocks of the corresponding general linear group. We show in this paper that an analogous result for the q-Schur algebras Sq(n,d) (when q is a primitive lth root of unity) can be derived in the same way from the blocks of an appropriate quantum general linear group...